Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


     First find the common difference   d   using the formula   nth = a +(n-1)d
      thus        4x-2y  =    (x+ y) + (4-1)d
                     4x-2y -(x+y) =   3d
                      3x -3y =   3d
                        x -y    =    d
               the first arithmetic mean        =   (x+y)+(x-y) =   2x
               the second arithmetic mean  =   2x + (x-y)  =   3x -y
1 5 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts